SPECT imaging of cytochrome c in pressure overload mice hearts. Issue 81 (15th August 2016) - Wang, Cong; Li, Xiao; Shen, Cheng; Ma, Leilei; Dong, Zhen; Zhu, Hong; Wang, Peng; Ge, Junbo; Sun, Aijun
Abstract : Clinically, pressure overload (PO) occurs in many clinical settings such as hypertension and valvular stenosis especially in the current aging society. Abstract : Clinically, pressure overload (PO) occurs in many clinical settings such as hypertension and valvular stenosis especially in the current aging society. During cardiac remodeling induced by PO, mitochondria were injured and cytochrome c was released. However, few studies have targeted cytochrome c for imaging. In this study, Technium-99m labeled cytochrome c antibody was developed to image PO hearts induced by transverse aortic constriction surgery. 99m Tc-Anti-cytochrome c was available to image and differentiate cytochrome c in normal mice hearts and PO hearts. The findings on images were consistent with detection by cardiac function and molecular biological assay. Hence, the noninvasive targeted cytochrome c imaging of mice hearts can be realized via 99m Tc-Anti-cytochrome c based SPECT.